Cognitive Changes after Surgery in Clinical Practice (In Clinical Practice,, 2018)
This book reviews current knowledge about cognitive dysfunction in surgical patients to provide a common knowledge base and terminology. It covers the topic in a way that considers all points of view, and enables the reader to be better equipped to manage cognitive dysfunction in all its manifestations in surgical patients. This book will hopefully also be a source of generating future ideas for research. Cognitive Changes after Surgery in Clinical Practice has an internationally renowned group of authors, and is aimed firstly at the perioperative team: surgeon, anaesthetist and surgical ward nurses; secondly, the researcher or geriatrician; and thirdly, public health specialists and hospital managers.